Exploring Code Clone Behavior in Modern Code Review - Uchoa, Italo; Sousa, Denis; Paixao, Matheus; Maia, Pedro; Uchôa, Anderson; Ragkhitwetsagul, Chaiyong (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2025: Anais do XXIV Simpósio Brasileiro de Qualidade de SoftwareDO - 10.5753/sbqs.2025.15740, 2025)
The Modern Code Review (MCR) process is iterative and asynchronous, enabling the early identification of issues during development. One of the main challenges in this context is the presence of code clones, fragments of code copied with small modifications that hinder maintainability. In this study, we analyzed 80k revisions from the CROP dataset using the Siamese detector, identifying 27,656 relevant clones across six systems. A manual validation indicated a predominance of Type-I (46.7%) and Type-III (45.3%) clones. We also identified 224 reviews in which clones appeared in a single revision (Single), 1,258 reviews in which clones appeared across multiple revisions (Recurring), and 236 reviews at the intersection of both categories. To deepen the analysis, we introduced two metrics, Duration and Distance, to assess how clones are introduced or removed during the review. This paper presents an expanded abstract of the study “An Exploratory Study on the lifecycle of Code Clones During Code Review”, published at SBES 2025.